Effect of ω-3 polyunsaturated fatty acids on C-reactive protein in patients with chronic kidney disease:a meta-analysis and systematic review - ZHOU Wen-yu; CHEN Wen-li; GAN Wen-yuan (Linchuang shenzangbing zazhi)
Objective We conducted a meta-analysis and systemic review to assess the effect ofω-3 polyurtsaturated fatty acids(ω-3 PUFAs) on markers of inflammation in chronic kidney disease(CKD).Methods We searched Pubmed,Cochrane library,EMbase to obtain randomized controlled trails(RCTs) data.The RevMan 5.2 was used for meta-analysis.Results Seventeen citations met the eligibility criteria Eleven articles described the specific randomized method and adopted adequate allocation concealment and blinding,3 articles did not describe the specific randomized method and use the single-blind design,and other 3 articles did not describe the specific randomized method and did not use the blind design.All of them reported loss of follow-up and withdrawal.829 patients had a mean value of 14 ± 9 weeks(4-48 weeks).ω-3 PUFAs could significantly reduce CRP levels in CKD with the weighted mean difference being-0.47,95%CI[-0.90,-0.04],P<0.05.Conclusions There are controversies on the effect of ω-3 PUFAs on markers of inflammation in CKD.In our study,Consumption of ω-3 PUFAs reduced CRP level in dialysis group,and may improve the inflammation state in CKD.ω-3 PUFAs,as a nutritional therapy almost has no adverse effect,can reduce CRP level and may improve the inflammation state in CKD.But for the clinical endpoint events and the long-term medication safety,the multicenter,prospective,randomized controlled experiments are needed.